Motivation and timing: clues for modeling the reward system - Galtress, Tiffany; Marshall, Andrew T.; Kirkpatrick, Kimberly (My University, 2012)
There is growing evidence that a change in reward magnitude or value alters interval timing, indicating that motivation and timing are not independent processes as was previously believed. The present paper reviews several recent studies, as well as presenting some new evidence with further manipulations of reward value during training vs. testing on a peak procedure. The combined results cannot be accounted for by any of the current psychological timing theories. However, in examining the neural circuitry of the reward system, it is not surprising that motivation has an impact on timing because the motivation/valuation system directly interfaces with the timing system. A new approach is proposed for the development of the next generation of timing models, which utilizes knowledge of the neuroanatomy and neurophysiology of the reward system to guide the development of a neurocomputational model of the reward system. The initial foundation along with heuristics for proceeding with developing such a model is unveiled in an attempt to stimulate new theoretical approaches in the field.
Keywords: Timing; Motivation; Reward; Computational modeling; Rat